Double Allogenic Mesenchymal Stem Cells Transplantations Could Not Enhance Therapeutic Effect Compared with Single Transplantation in Systemic Lupus Erythematosus - Dandan Wang; Kentaro Akiyama; Huayong Zhang; Takayoshi Yamaza; Xia Li; Xuebing Feng; Hong Wang; Bingzhu Hua; Bujun Liu; Huji Xu; Wanjun Chen; Songtao Shi; et al. (Clinical and Developmental Immunology)
The clinical trial of allogenic mesenchymal stem cells (MSCs) transplantation for refractory SLE patients has shown significant safety and efficacy profiles. However, the optimum frequency of the MSCs transplantation (MSCT) is unknown. This study was undertaken to observe whether double transplantations of MSCs is superior to single transplantation. Fifty-eight refractory SLE patients were enrolled in this study, in which 30 were randomly given single MSCT, and the other 28 were given double MSCT. Patients were followed up for rates of survival, disease remission, and relapse, as well as transplantation-related adverse events. SLE disease activity index (SLEDAI) and serologic features were evaluated. Our results showed that no remarkable differences between single and double allogenic MSCT were found in terms of disease remission and relapse, amelioration of disease activity, and serum indexes in an SLE clinical trial with more than one year followup. This study demonstrated that single MSCs transplantation at the dose of one million MSCs per kilogram of body weight was sufficient to induce disease remission for refractory SLE patients.